SOME BIOLOGICAL ASPECTS AND OBSERVATIONS OF A NEW LICE FLOUR OF YUCCA Phenacoccus herreni (HOMOPTERA: PESUDOCOCCIDAE) IN COLOMBIA - VARELA, ANA MILENA; BELLOTII, ANTHONY C. (Revista Colombiana de Entomología, 1981)
There are several species of mealybugs that attack cassava; these include Phenacoccus manihoti, P. gossypii and P. grenadensis. Reports, in recent years of severe yield losses caused by the species P. manihoti in Africa, have increased interest among entomologists to further investigate these pests in the neotropics. In 1978, a new species of mealy-bug, later described as P. herreni, was found in Colombia. Plant damage symptoms of P. herreni are very similar to those of P. manihoti; the initial attack and most severe damage are to the growing point of the cassava plant. However, the biology of the two species differs in that P. herreni is bisexual, while P. manihoti reproduces parthenogenetically. This study of the biology of P. herreni shows that the female passes through 3 instars before reaching the adult stage; the complete cycle of the egg through adult is 49.5 days. The male passes through 4 instars before the winged, adult stage; the total cycle is 29.5 days. The ovipositional period of the female is 18.4 days during which an average of 773.6 eggs are oviposited in the ovisac. The female increases in size through the adult stage while the male increases in size through the second instar, during which it forms a cacoon and gradually transforms into an adult.